On Some Properties of Doubt Bipolar Fuzzy H-ideals in BCK/BCI-algebras (European Journal of Pure and Applied Mathematics, 2018)
In this research article, we study some properties of doubt bipolar fuzzy H-ideals inBCK/ BCI-algebras. Doubt bipolar fuzzy H-ideals are connected with doubt bipolar fuzzy subalgebras and doubt bipolar fuzzy ideals. Moreover, doubt bipolar fuzzy H-ideals are characterized using doubt positive t-level cut set, doubt negative s-level cut set and H-Artin BCK/BCI-algebras.
Keywords: BCK=BCI-algebras; Doubt fuzzy ideals; Doubt fuzzy H-ideals; Doubt bipolar fuzzy subalgebras; Doubt bipolar fuzzy ideals; Doubt bipolar fuzzy H-ideals